[(18)F]ASEM, a radiolabeled antagonist for imaging the α7-nicotinic acetylcholine receptor (α7-nAChR) with positron emission tomography (PET) - Horti, Andrew G. (2014)
The α7-nicotinic cholinergic receptor (α7-nAChR) is a key mediator of brain communication and has been implicated in a wide variety of central nervous system disorders. None of the currently available PET radioligands for α7-nAChR are suitable for quantitative PET imaging, mostly due to insufficient specific binding. The goal of this study was to evaluate the potential of [(18)F]ASEM ([(18)F]JHU82132) as an α7-nAChR radioligand for PET. METHODS: Inhibition binding assay and receptor functional properties of ASEM were assessed in vitro. The brain regional distribution of [(18)F]ASEM in baseline and blockade were evaluated in DISC1 mice (dissection) and baboons (PET). RESULTS: ASEM is an antagonist for the α7-nAChR with high binding affinity (K(i) = 0.3 nM). [(18)F]ASEM readily entered the baboon brain and specifically labeled α7-nAChR. The in vivo specific binding of [(18)F]ASEM in the brain regions enriched with α7-nAChRs was 80–90%. SSR180711, an α7-nAChR selective partial agonist, blocked [(18)F]ASEM binding in the baboon brain in a dose-dependent manner, suggesting that the binding of [(18)F]ASEM was mediated by α7-nAChRs and the radioligand was suitable for drug evaluation studies. In the baboon baseline studies, the brain regional volume of distribution (V(T)) values for [(18)F]ASEM were 23 (thalamus), 22 (insula), 18 (hippocampus) and 14 (cerebellum), whereas in the binding selectivity (blockade) scan, all regional V(T) values were reduced to less than 4. The range of regional binding potential (BP(ND)) values in the baboon brain was from 3.9 to 6.6. In vivo cerebral binding of [(18)F]ASEM and α7-nAChR expression in mutant DISC1 mice, a rodent model of schizophrenia, was significantly lower than in control animals, which is in agreement with previous post-mortem human data. CONCLUSION: [(18)F]ASEM holds promise as a radiotracer with suitable imaging properties for quantification of α7-nAChR in the human brain.